The Role of Toll-Like Receptors in Hematopoietic Malignancies - Monlish, Darlene A.; Bhatt, Sima T.; Schuettpelz, Laura G. (Frontiers in Immunology, 2016)
Toll-like receptors (TLRs) are a family of pattern recognition receptors that shape the innate immune system by identifying pathogen-associated molecular patterns and host-derived damage-associated molecular patterns. TLRs are widely expressed on both immune cells and non-immune cells, including hematopoietic stem and progenitor cells, effector immune cell populations, and endothelial cells. In addition to their well-known role in the innate immune response to acute infection or injury, accumulating evidence supports a role for TLRs in the development of hematopoietic and other malignancies. Several hematopoietic disorders, including lymphoproliferative disorders and myelodysplastic syndromes, which possess a high risk of transformation to leukemia, have been linked to aberrant TLR signaling. Furthermore, activation of TLRs leads to the induction of a number of proinflammatory cytokines and chemokines, which can promote tumorigenesis by driving cell proliferation and migration and providing a favorable microenvironment for tumor cells. Beyond hematopoietic malignancies, the upregulation of a number of TLRs has been linked to promoting tumor cell survival, proliferation, and metastasis in a variety of cancers, including those of the colon, breast, and lung. This review focuses on the contribution of TLRs to hematopoietic malignancies, highlighting the known direct and indirect effects of TLR signaling on tumor cells and their microenvironment. In addition, the utility of TLR agonists and antagonists as potential therapeutics in the treatment of hematopoietic malignancies is discussed.